EFFECT OF REMOTE WORKING ON PSYCHOLOGICAL WELL-BEING OF IT EMPLOYEES: AN EMPIRICAL ANALYSIS DURING COVID-19 PANDEMIC - Sonia, Dr.C.; Krishnamoorthy, Mr.D. (The journal of contemporary issues in business and government, 2022)
Purpose:The COVID-19 pandemic sweeping the world has triggered paradigm shifts in the alternative work arrangements for diminishing the spread of the virus. Suddenly, many IT companies around the globe are forcing their employees to work remotely. As a result, this has blurred the line between work and family roles because professional and personal obligations often pull employees in opposite directions. This research aims to explore the influence of remote work challenges (Emotional Loneliness, Access to Organizational Resources, Work Family Conflict, Work Disengagement) on Psychological Well Being. Design/methodology/approach:A convenience sample of 340 Chennai IT professionals who were working from home for the past one year (Jan 2021-Dec 2021) was invited to fill an online questionnaire (Google Forms). A closed-ended questionnaire was used with three subsections covering the following areas, 1) Demographic Profile 2) Challenges faced in remote work 3)Psychological well-being. Statistical analyses were conducted using SPSS 23.0 and AMOS 23.0. The study employing structural equation modeling (SEM) to analyze the influence of remote work challenges on psychological well-being. Findings: The proposed model yields good fit indices. One finding shows that dimension of remote work challenges such as emotional loneliness, access to organizational resources, work family conflict and work disengagement influence the psychological well-being of employees. In the model, gender, parental status, working hours and marital status are considered as moderating variables. The result reveals that compared to men, women felt work family conflict is significantly influencing psychological well-being during remote work. Surprisingly, the relationship between emotional loneliness, access to organizational resources and work disengagement did not differ by gender. In parental status, employees with children show significant influence of work family conflict on psychological well-being when compared to employees with no children. The study also interprets that married employees face interference of work family conflict on psychological well-being when compared to unmarried employees. Employees working more than eight hours feel emotional loneliness, access to organizational resources; work family conflict and work disengagement impact psychological well-being of an individual.